Investigation on plasma properties for deposition of titanium nitride film using reactive magnetron sputtering system - Soo, Reh How (2018)
Deposition of thin film using plasma sputtering system had been widely discovered and developed extensively for many years in technological and industrial process especially formation of titanium nitride (TiN) films due to its high hardness, good wear resistance, low friction coeffcient and chemical stability. These TiN films have been commonly used in microelectronics and coatings area. However, formation of TiN thin flms in nano size device using the plasma sometimes is not stable and hard to achived with optimum level. As a result, fundamental of understanding on the sputter mechanism of atom in reactive magnetron sputtering plasma is very important in order to implement the plasma sputtering for the formation of conformal TiN thin film in a very fine hole in integrated circuit device. In this work, the working power and nitrogen gas flow rate were varied during the deposition process and spectrocopic measurement. Plasma diagnostics such as optical emission spectrocopy and Langmuir probe were used for characterizing plasmas and for better understanding of physical and chemical processes occur during the deposition of TiN films in the plasma sputtering. On the other hand, the formation of TiN films using reactive magnetron sputtering system also have been conducted. The thickness and roughness of TiN films were examined using surface profiler and atomic force microscope respectively. Thus, correlation of relative depostion of TiN films and plasma diagnostics have been successfully obtained to improve the understanding of sputter mechansim process for TiN films. More quantitative analysis also had been done throughout the findings to confirm the effect of different parameters used significantly change the properties of TiN films.